Tawakkal As An Affective Dimension Of Islamic Religious Education: A Validity And Reliability Test Of An Instrument On University Students - Roidah Lina; Qiyadah Robbaniyah (At Turots: Jurnal Pendidikan Islam, 2026)
Islamic religious education (IRE) is oriented not merely toward cognitive mastery but, more fundamentally, toward the internalization of values and inner attitudes that constitute the affective domain, among which tawakkal (trust in God) is central. However, the assessment of affective outcomes in IRE remains dominated by cognitive approaches, and measurement tools rooted directly in the Islamic intellectual tradition (turats) are still scarce. This study aims to test the validity and reliability of a tawakkal instrument derived from the eight degrees of tawakkal formulated by Ibn Qayyim al-Jauziyyah in Madarij as-Salikin. The instrument consists of thirty items distributed across eight dimensions—Ma'rifatullah, Itsbatul Asbab, Tauhid Qalbi, I'timad and Sukun, Husnu Zhan, Istislamul Qalb, Tafwidh, and Ridha—using a five-point Likert scale with eight reverse-scored items. The instrument was administered to 128 female students of Islamic Education and Arabic Education study programs. Data were analyzed through corrected item-total correlation for item validity, the Kaiser-Meyer-Olkin (KMO) measure and Bartlett's test of sphericity for sampling adequacy, and Cronbach's alpha for internal-consistency reliability. The results show a KMO value of 0.859 and a significant Bartlett's test (p < 0.001), indicating that the data are adequate for analysis. Twenty-eight of the thirty items met the validity criterion of corrected item-total correlation above 0.30 (range 0.203 to 0.691), while all items exceeded the critical r-table value of 0.1736. The overall instrument reliability was excellent, with Cronbach's alpha of 0.895, although the per-dimension coefficients were more modest because of the small number of items per subscale. Respondents exhibited a high level of tawakkal (item mean = 4.26 on a five-point scale). The study concludes that the tawakkal instrument grounded in Ibn Qayyim's framework is valid and reliable as a whole and is feasible for use as an instrument to assess the affective achievement of IRE, with a recommendation for further confirmatory factor analysis on a larger sample.